Implementación de una Red Wifi en la Unidad Educativa réplica Eugenio Espejo para Mejorar la Calidad Educativa y la Gestión Administrativa. - Menéndez Vera, Karen Jessenia (2024)
This case study focuses on the implementation of a Wi-Fi network at the Unidad Educativa Réplica Eugenio Espejo, with the aim of improving educational quality through access to digital resources and optimizing the administrative management of the institution. The research is structured in three key phases: first, a comprehensive diagnosis of the current connectivity situation in the educational unit is carried out, evaluating the existing infrastructure and specific needs. Then, an appropriate Wi-Fi network infrastructure is designed, using simulation tools such as Packet Tracer, to ensure comprehensive coverage in all areas of the institution. This design not only seeks to provide Internet access, but also to create a digital environment that supports academic and administrative activities. Finally, the possible impact of the Wi-Fi network on educational quality and on the administrative management of the institution is evaluated, analyzing both qualitative and quantitative aspects to measure the effect of connectivity on students' academic performance and on the efficiency of administrative processes. The study concludes that a well-designed Wi-Fi network can be a key factor in transforming education and administration in the institution, facilitating access to online educational resources and improving communication and internal management.